Automated system for measuring the surface dilational modulus of liquid–air interfaces. (27th April 2016) - Stadler, Dominik; Hofmann, Matthias J; Motschmann, Hubert; Shamonin, Mikhail
Abstract: The surface dilational modulus is a crucial parameter for describing the rheological properties of aqueous surfactant solutions. These properties are important for many technological processes. The present paper describes a fully automated instrument based on the oscillating bubble technique. It works in the frequency range from 1 Hz to 500 Hz, where surfactant exchange dynamics governs the relaxation process. The originality of instrument design is the consistent combination of modern measurement technologies with advanced imaging and signal processing algorithms. Key steps on the way to reliable and precise measurements are the excitation of harmonic oscillation of the bubble, phase sensitive evaluation of the pressure response, adjustment and maintenance of the bubble shape to half sphere geometry for compensation of thermal drifts, contour tracing of the bubbles video images, removal of noise and artefacts within the image for improving the reliability of the measurement, and, in particular, a complex trigger scheme for the measurement of the oscillation amplitude, which may vary with frequency as a result of resonances. The corresponding automation and programming tasks are described in detail. Various programming strategies, such as the use of MATLAB ® software and native C++ code are discussed. An advance in the measurement technique is demonstrated by a fully automated measurement. The instrument has the potential to mature into a standard technique in the fields of colloid and interface chemistry and provides a significant extension of the frequency range to established competing techniques and state-of-the-art devices based on the same measurement principle.